(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
Composite nickel coatings composed of Ni; Ni + TiN are studied. The method for elecrtroless nickel deposition EFFTOM-NICKEL with TiN nanosized strengthening particles (50nm) is applied. The coatings are deposited on austempered ductile iron (ADI) samples. The composition of cast iron samples is: Fe-3,63C-2,59Si-0,30Mn-0,010S-0,034P-0,53Cu wt. %. The samples are put under isothermal hardening at 900oС for an hour and isothermal retention at 290 oС for 2 hours with the aim to receive a lower bainite structure. The wear resistance experimental testing is carried out using Taber-Abraser test machine by disk to disk classical method. The microstructure observations of the coatings and padding are performed using an optical microscope GX41 OLIMPUS also the coatings’ microhardness by Knoop Method is examined. The wear resistance, microstructure, thickness and microhardness of the as plated and thermally processed at 290oС for 6 hours coatings are defined.